Acceptorless Dehydrogenation of N‐Heterocycles by Merging Visible‐Light Photoredox Catalysis and Cobalt Catalysis - He, Ke‐Han; Tan, Fang‐Fang; Zhou, Chao‐Zheng; Zhou, Gui‐Jiang; Yang, Xiao‐Long; Li, Yang (Angewandte Chemie International Edition, 2017)
Herein, the first acceptorless dehydrogenation of tetrahydroquinolines (THQs), indolines, and other related N‐heterocycles, by merging visible‐light photoredox catalysis and cobalt catalysis at ambient temperature, is described. The potential applications to organic transformations and hydrogen‐storage materials are demonstrated. Primary mechanistic investigations indicate that the catalytic cycle occurs predominantly by an oxidative quenching pathway. Cobalt and blue: The titled method is utilized for the reversible dehydrogenation‐hydrogenation protocol at ambient temperature under mild reaction conditions. Primary mechanistic investigations indicate that the catalytic cycle relies predominantly on an oxidative quenching pathway.